KAJIAN PENGANGKUTAN PERSAMPAHAN DI KOTA SEMARANG BERDASARKAN GRAFIK PENGENDALI KECEPATAN - Maryono, Maryono; Wahyudi, Bramanthyo Heru (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Some issues arouse an opinion that the activity of garbage transportation systems in Semarang aren’t work properly.  This  transportation  systems  management  in  Semarang  are  able  to  be evaluated from aspect of  time-limited transportation systems that which determines the efficient routes,  so  that  it could  be  solve  the  issues  of  garbage  transportation  systems  based  on  the minimum time-limit (not always the route with the nearest distances) from the dump-truck to the direction  of  TPA.  It  found that  the  velocity  of  dump-truck  is  28  km/hours  above  the  minimum services  standard,  which  is 25  km/hours.  It  also  found  that  quality  of  the  effective  time  of garbage transportation systems in Semarang is 1,026 or PKP ≈ 1, which depict that there is a lot of garbage that not well-distributes to the TPA in several zone. Whereas the efficient velocity of the dump-truck are about 26-28 km/hours. Overall we can conclude that the time-efficiency of garbage transportation systems in Semarang is in a middle conditions.